SISTEM PENDINGINAN AIR UNTUK PANEL SURYA DENGAN METODE FUZZY LOGIC - Maruto Swatara Loegimin; Bambang Sumantri; Mochamad Ari Bagus Nugroho; Hasnira Hasnira; Novie Ayub Windarko (Politeknik Negeri Batam, 2020)
Sun light is one form of energy from natural resources. These solar natural resources have been widely used to supply electrical power in communication satellites through solar cells. This solar cell can produce unlimited amounts of electrical energy directly taken from the sun. The solar panel itself has the maximum body temperature which influences the output of the solar panel. Solar cell panels have a decreased ability to generate electricity if it overheats or goes through the limits of effectiveness. Therefore, a cooling tower system is developed using the Fuzzy Logic method through this study with the aim of maximizing the efficiency of solar cell panels in generating electricity and analyzing Solar Panel systems( Photovoltaic). The data analyzed are: 1) The method of cooling solar panels using the cooling tower system with fuzzy logic methods, 2) Efficiency of Solar Cell Panels in generating electricity, 3) Electric power produced by solar cell panels. The results of this study explain that the use of fuzzy logic can regulate the speed of water for cooling on panels so that it can be said that the cooling system for solar panels is suitable for use in the tropics, because sunlight is very abundant and is in the equatorial area.